2000
DOI: 10.1021/ma992128a
|View full text |Cite
|
Sign up to set email alerts
|

Brownian Dynamics Simulations of Dendrimers under Shear Flow

Abstract: Brownian dynamics simulations of perfect dendrimers up to the sixth generation have been performed under the influence of simple shear flow. Hydrodynamic and excluded volume interactions have been taken into account explicitly. The onset of shear-thinning is observed to occur at lower shear rates for larger dendrimers (i.e. more generations). As the generation increases, the zero shear rate intrinsic viscosity reaches a maximum and begins to fall. The radius of gyration, the hydrodynamic radius, the translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
124
0
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(144 citation statements)
references
References 28 publications
15
124
0
5
Order By: Relevance
“…As in the previous studies [12][13][14][15][16] we consider a bead-rod freely-joint model of a dendrimer and an oppositely charged linear PE chain, Fig. 1.…”
Section: Model Of a Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the previous studies [12][13][14][15][16] we consider a bead-rod freely-joint model of a dendrimer and an oppositely charged linear PE chain, Fig. 1.…”
Section: Model Of a Complexmentioning
confidence: 99%
“…All beads of a complex are characterized by the friction coefficient ζ . The finite-difference numerical scheme implemented here is based on the Ermak-McCammon equation [12][13][14][15][16]19].…”
Section: Simulation Algorithmmentioning
confidence: 99%
“…Lyulin et al revealed that simulated intrinsic viscosity values for these dendrimers peak near generation 5 (Nϭ190). 14,39 At each N, HP molecules with DB ϭ0.4, 0.6, and 0.8 were specified. For each of these DBs, at each N, two to three molecules were created having distinct Wiener indices selected according to a systematic procedure ͑detailed below͒.…”
Section: ͑21͒mentioning
confidence: 99%
“…These parameters are in keeping with work of Lyulin et al on similar molecules. 14,39 Simulation runs of 3ϫ10 5 to 1ϫ10 6 timesteps were used for equilibration, depending on molecular size. Typically, production runs spanned 2ϫ10 7 steps for N ϭ94 molecules, 1ϫ10 7 to 2ϫ10 7 steps for Nϭ190 molecules, and 3ϫ10 6 to 6ϫ10 6 steps for Nϭ382 molecules.…”
Section: ͑212͒mentioning
confidence: 99%
“…For example, the intrinsic viscosity of a dendrimer with the hydrodynamic interaction shows a maximum as the generation increases, 7,35,36) while for linear and star polymers it increases monotonically with the molecular weight. 2,4,37) Since the intrinsic viscosity is associated with the relaxation modes, 2,6) it is interesting how the picture of the relaxation process discussed in the present study relates to such unique features in the presence of the hydrodynamic interaction.…”
Section: Summary and Discussionmentioning
confidence: 99%